MODERN TRANSFORMATION TRENDS OF CORPORATE STRUCTURES IN THE GLOBAL CHALLENGES - Кудирко, Л. П.; Лазаренко, А. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
Examined trends in corporate organizational structures in the conditions of increasing globalization processes, identified the factors that determine widespread benefits and risks of international business practice of corporate structures, formulated proposals of the domestic management system adjusting to the challenges of civilization development.